Is there a role for locoregional surgery in stage IV breast cancer?. Issue 1 (February 2015) - Quinn, Edel M.; Kealy, Rebecca; O'Meara, Siobhan; Whelan, Maria; Ennis, Rachel; Malone, Carmel; McLaughlin, Ray; Kerin, Michael J.; Sweeney, Karl J.
Abstract: Current guidelines do not recommend locoregional surgery for Stage IV breast cancer at presentation despite some studies suggesting a survival benefit. We aimed to assess outcomes in patients with Stage IV breast cancer who underwent surgery. In a cohort study of all Stage IV breast cancers diagnosed at our tertiary-referral specialist centre between 2006 and 2012, we assessed patient survival in the context of demographics, histopathology, metastatic burden, and type of surgery performed. One hundred and nine patients were included; 52 underwent surgery. Patients in the surgery group had longer 5-year-survival ( p = 0.003). Survival was also significantly longer in those with just one site of metastatic disease ( p < 0.001). Patients with axillary cytology positive for regional metastases were less likely to proceed to surgery. Locoregional surgery does confer a survival advantage in Stage IV breast cancer. Assessment of preoperative axillary cytology may preclude some patients from proceeding to potentially beneficial locoregional surgery.